Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper examines three areas of key policy importance for Greece in the coming years. The paper documents the loss of international competitiveness in recent years, as well as the accompanying widening of the current account deficit. It analyzes fiscal consolidation episodes in advanced economies, and confirms the conclusion found in the literature that, for durable consolidation, control of current spending is superior to revenue increases. The paper also estimates European banks' vulnerability to rapid credit growth and economic slowdowns.